2011
DOI: 10.1016/j.jtcvs.2010.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Natural orifice transluminal endoscopic surgery: A transtracheal approach for the thoracic cavity in a live canine model

Abstract: Transtracheal thoracic exploration is technically feasible. Increasing surgical experience together with improvement in endoscopic techniques will further facilitate the development of natural orifice transluminal endoscopic surgery for thoracic diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…Minimizing tissue trauma and subsequent stress response is a goal of surgery [ 42 ] and CRP is often included as an objective marker in studies investigating this response in dogs [ 37 , 42 , 43 , 45 ]. CRP has on several occasions been used in studies investigating new surgical procedures for the veterinary clinic [ 26 , 29 , 31 , 35 ], in studies using dogs as model for human disease [ 27 , 28 , 30 ], and in studies comparing different surgical procedures [ 32 , 34 ]. In the last group several studies have compared surgical trauma by comparing different surgical procedures in different tissues [ 9 , 33 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Minimizing tissue trauma and subsequent stress response is a goal of surgery [ 42 ] and CRP is often included as an objective marker in studies investigating this response in dogs [ 37 , 42 , 43 , 45 ]. CRP has on several occasions been used in studies investigating new surgical procedures for the veterinary clinic [ 26 , 29 , 31 , 35 ], in studies using dogs as model for human disease [ 27 , 28 , 30 ], and in studies comparing different surgical procedures [ 32 , 34 ]. In the last group several studies have compared surgical trauma by comparing different surgical procedures in different tissues [ 9 , 33 ].…”
Section: Reviewmentioning
confidence: 99%
“…One study has, however, shown significant lower concentrations of CRP as a result of treatment with low doses of ketamine during and after surgery [ 40 ], as also demonstrated in humans [ 51 ]. Ketamine was included in the anesthetic protocols of 6 studies included in the review [ 22 , 27 , 28 , 32 , 34 , 41 ], and CRP concentrations in these studies could potentially be affected when compared to the remaining studies. However, other studies in human medicine have shown conflicting results [ 52 , 53 ] and the conclusions for dogs were all based on a single study affected by considerable risks of bias (Fig.…”
Section: Reviewmentioning
confidence: 99%
“…These procedures include subxiphoid pericardial window creation, coronary surgery, thymectomy, and pulmonary metastasectomy (10)(11)(12)(13)(14). We have used animal models to determine alternative approaches such as natural orifice transluminal surgery through transoral, transtracheal (15)(16)(17)(18), and transumbilical routes (19). However, most of these procedures are currently not feasible to be performed in humans.…”
Section: Introductionmentioning
confidence: 99%
“…The diaphragmatic incision was then sequentially dilated to 2.5 cm using a metallic tube, as previously described. 9 Two metallic tubes (10 mm and 15 mm) were then inserted into the thoracic cavity via the diaphragmatic incision and used as a working port for stapled lung wedge resection. After adequate exploration of the thoracic cavity with the bronchoscope via the 10-mm port, the stapler was gently applied to the targeted lung lobe (left upper lobe, n = 3; right upper lobe n = 3; right middle lobe, n = 3; right lower lobe, n = 2) via the 15-mm port.…”
Section: Methodsmentioning
confidence: 99%